Ladle filler sand for rebaking ladle and preparation method of ladle filler sand

Through the use of chromium ore, quartz sand, 锆 锆 通过, electric melting magnesium, light -roasted white cloud stone sand, diatomic soil and carbon material in the baking baked sand, the low opening rate of the baking bag is solved, It can improve the self -opening rate and production efficiency without baking.

CN119350007AActive Publication Date: 2025-01-24HENAN TONGYU METALLURGY MATERIALS GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411493713.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

After replacing the water outlet, the moisture content of the refrigeration bag is relatively high and the self-opening rate is low, which causes the liquid molten steel to not flow out automatically. The operator needs to use oxygen pipes to ignite and assist in drainage, which affects the quality and production efficiency of the liquid molten steel.

Method used

Adopt a supplementary baked bag drainage sand made of chromium mineral sand, quartz sand, 锆 采, electric molten magnesium, light -burned white cloud stone sand, diatomic soil and carbon material, and through diatomic soil and light -burned white cloud stone Coordination, adsorb water and reduce the pressure of the sintering layer, and increase the self -opening rate.

Benefits of technology

It can increase the self -opening rate of the steel bag without baking, reduce the heat flux during the retention period of the steel, delay sintering phenomenon, improve the launch turnover efficiency of the steel bag, and avoid the self -opening rate of the self -opening rate due to excessive moisture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides rebaking ladle stuffing sand and a preparation method thereof, and belongs to the technical field of steelmaking continuous casting. The invention relates to baking ladle filling sand which is prepared from the following raw materials in parts by weight: 0-75 parts of chromium ore, 0-75 parts of quartz sand, 0-50 parts of zircon sand, 0-50 parts of fused magnesite, 10-25 parts of light-burned dolomite sand, 3-7 parts of diatomite and 1-3 parts of a carbonaceous material, and contains at least one of chromium ore, quartz sand, zircon sand and fused magnesite. The method is used for solving the practical problems of relatively high moisture and low self-opening rate after the upper nozzle of the rebaking ladle is replaced, so that the steel ladle does not need to be baked after the upper nozzle of the steel ladle is replaced and fire clay is smeared, and after the ladle filler sand of the rebaking ladle is directly added, the phenomenon that the self-opening rate is reduced due to gasification and escape of fire clay in the nozzle is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steelmaking and continuous casting, and particularly relates to a baking ladle drainage sand and a preparation method thereof. Background Art

[0002] Ladle drainage sand is a refractory material used to fill the ladle nozzle. Its function is to cast the molten steel after it has been refined to the target requirements. During casting, the ladle slide is opened, and the lower drainage sand flows out, forming a cavity in the lower middle part of the nozzle seat brick. The molten steel uses static pressure to break the sintered layer of drainage sand on the upper part of the nozzle seat brick, rush out of the nozzle, and realize automatic pouring. If the sintered layer of drainage sand is too thick and the compressive strength is greater than the static pressure of the molten steel, the molten steel cannot flow out automatically, and the operator needs to ignite the oxygen pipe to assist in drainage, which is the so-called oxygen burning. The oxygen burning phenomenon has a great impact on the quality of molten steel, such as overoxidation of molten steel, alloy burning, etc. Most of the steel products after oxygen burning face downgrading or scrapping. At the same time, the oxygen burning operation process is also accompanied by the risk of scalding to the operator. If the oxygen burning operation is unsuccessful, it will also cause continuous pouring interruption, bringing huge economic losses and safety hazards to steel companies.

[0003] In order to improve the automatic pouring rate of the ladle, technical personnel in the industry have optimized the ladle scheduling measures, such as shortening the retention time of molten steel, expanding the nozzle aperture, etc.; at the same time, they have continuously improved the design of drainage sand, such as adjusting the appropriate refractoriness, reducing thermal conductivity, adjusting the sintering speed, etc., to improve the adaptability of drainage sand to the service environment; all of the above measures have generally achieved corresponding improvements. However, from the statistical analysis results of the ladle self-opening rate, for the newly launched ladles with a short baking time and the ladles with the upper nozzle replaced in the middle of the ladle life, that is, the so-called re-baking ladles or minor repair ladles, the self-opening rate is still obviously insufficient. At present, the solution to the problem of low self-opening rate of re-baking ladles in the industry is to reduce the moisture content of the drainage sand product as much as possible, or to extend the baking time of the ladle after replacing the upper nozzle, and the self-opening rate will be improved. However, the actual problems are as follows: (1) The moisture content of drainage sand products is originally controlled to be very low, usually below 0.5%. There is very limited room for further reduction, and it requires strict production control and process upgrades to achieve. For drainage sand production companies, this means a substantial increase in product costs; (2) Prolonging the ladle baking time not only increases fuel and energy consumption, but also affects the effective scheduling of the ladle, delaying the production rhythm, and incurring huge direct and indirect economic costs.

[0004] Therefore, according to actual production needs, it is also necessary to develop corresponding drainage sand products to address the current situation where the moisture content is relatively high and the self-opening rate is low after the water inlet of the baking bag is replaced, so as to make up for the shortcoming of the low self-opening rate. Summary of the invention

[0005] In view of this, the present invention provides a drainage sand for a supplementary baking ladle to solve the practical problems of relatively high moisture content and low self-opening rate after the upper water inlet of the supplementary baking ladle is replaced, so that the ladle does not need to be baked after the upper water inlet is replaced and the fire mud is applied. After the drainage sand for the supplementary baking ladle is directly added, the self-opening rate will not decrease due to the vaporization and escape of water from the fire mud in the water inlet.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a kind of drainage sand for baking bags, which is made of the following raw materials in parts by weight: 0-75 parts of chromium ore, 0-75 parts of quartz sand, 0-50 parts of zircon sand, 0-50 parts of fused magnesia, 10-25 parts of light-burned dolomite sand, 3-7 parts of diatomaceous earth, 1-3 parts of carbonaceous material, and contains at least one of chromium ore, quartz sand, zircon sand and fused magnesia.

[0007] Preferably, the chromium ore contains Cr2O3 in a weight percentage of ≥45%, Fe2O3 in a weight percentage of ≤28%, Al2O3 in a weight percentage of ≤16%, MgO in a weight percentage of ≤9%, and has a particle size of 0.2 mm-0.5 mm.

[0008] Preferably, the quartz sand contains SiO2 at a weight percentage of ≥95% and a particle size of 0.3 mm-1.5 mm.

[0009] Preferably, the zircon sand contains ZrO2 in a weight percentage of ≥58%, SiO2 in a weight percentage of ≤38%, and a particle size of 0.1 mm-0.5 mm.

[0010] Preferably, the fused magnesia contains MgO at a weight percentage of ≥97% and a particle size of 0.3 mm-1.5 mm.

[0011] Preferably, the light-burned dolomite sand contains MgO in a weight percentage of ≥55%, CaO in a weight percentage of ≥38%, and has a particle size of 0.3 mm-1.5 mm.

[0012] Preferably, the diatomite contains SiO2 at a weight percentage of ≥88%, Al2O3 at a weight percentage of ≤8%, and a bulk density of ≤0.5 g / cm 3 , particle size is 0.1mm-0.5mm.

[0013] Preferably, the carbonaceous material is any one of carbon black or flake graphite or a mixture of the two, containing C 固 The weight percentage is ≥98%.

[0014] Preferably, the mass percentage of the effective ingredients of the drainage sand for baking supplement is: MgO: 6.0%-65.0%, SiO2: 3.0%-85.0%, ZrO2: 0%-30.0%, Cr2O3: 0%-34.0%, Fe2O3: 0%-21.0%, CaO: 3.5%-10.0%, Al2O3: 0.2%-12.5%, and the rest are unavoidable impurities.

[0015] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing at least one of chromium ore sand, quartz sand, zircon sand and fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product to a moisture content of less than 0.1% after drying, and cool it naturally to below 60°C to obtain the finished product, which is then measured and packaged as required.

[0016] Preferably, the air supply temperature of the drying process is 200°C-450°C.

[0017] The inventors have found in practice that the self-opening rate of the repaired baking ladle is generally low, and through long-term in-depth observation and comprehensive analysis, they found that the main reason for the low self-opening rate of the repaired baking ladle is: before replacing and installing the upper water inlet, in order to prevent the "steel penetration" accident during the operation of the ladle, a large amount of fire mud is usually applied on the outer wall of the water inlet core, and then loaded into the water inlet seat brick. After the slide plate is closed, the inner cavity of the water inlet becomes a closed space. The moisture in the fire mud vaporizes and diffuses in the high temperature environment of the ladle water inlet seat brick (the temperature in this area can reach 500-1500℃ when the ladle is running to hold steel), penetrates into the drainage sand with extremely high gas partial pressure, and forms holes. After the molten steel flows through the holes, it mixes with the drainage sand to form a mixture of solidified steel and sintered block (sand), which blocks the water inlet channel and causes oxygen burning and drainage phenomenon.

[0018] Based on this, the present invention combines the new discovery that a large amount of fire clay is needed to replace the upper nozzle of the repair ladle, resulting in high moisture content in the nozzle cavity, and introduces two specific materials, diatomite and light-burned dolomite, on the basis of the conventional chromium, zirconium or magnesium drainage sand main materials. Among them, diatomite is a porous, loose, natural siliceous rock with a refractoriness of 1650-1750℃, and has good water absorption. In the present invention, its role is to absorb excess moisture (steam) in the inner cavity of the nozzle seat brick, reduce the gas partial pressure of water at high temperature, and has a high refractoriness, which can significantly improve the self-opening rate of the ladle. The light-burned dolomite is obtained by calcining dolomite raw material at 1000°C to release gas. It is a porous raw material containing MgO and CaO components. Its main function in the drainage sand of the present invention is to supplement and strengthen the water adsorption effect of diatomaceous earth. At the same time, considering that the water content of the fire clay used for supplementary baking of the ladle varies with environmental factors such as weather and production site temperature, when the water content of the inner cavity of the water inlet of an individual ladle is too high, the diatomaceous earth in the drainage sand cannot be completely adsorbed, and it will continue to gasify, diffuse and penetrate into the drainage sand. The CaO component in the light-burned dolomite has a very strong adsorption capacity for water vapor, and will quickly hydrate and generate cracks when it encounters water vapor. This can effectively reduce the gas partial pressure of water and form uniform cracks inside the drainage sand to reduce the compressive strength of the sintered layer, thereby achieving the effect of improving the self-opening rate of the ladle.

[0019] The chromium ore sand, quartz sand, zircon sand and fused magnesia sand used in the drainage sand of the present invention are all common raw materials for the production of conventional chromium, zirconium or magnesia drainage sand, and can be flexibly selected and matched according to the specific steel type and process requirements of steel enterprise users.

[0020] The drainage sand product of the present invention can be directly added to the nozzle and put into operation without baking after the upper nozzle of the reheating ladle is replaced and the fire mud is applied; the amount of addition refers to the size of the nozzle aperture, and the nozzle is filled and a sand mound of 15 cm high is naturally formed. The drainage sand product of the present invention can also be used on a normally operating ladle.

[0021] Compared with the prior art, the present invention has the following beneficial effects: 1) Among the raw materials used for the drainage sand of the present invention, diatomite is a highly water-absorbent refractory raw material, which cooperates with light-burned dolomite to form a complementary effect of low-temperature and high-temperature water absorption, and completely solves the problem of high moisture content in the inner cavity of the nozzle seat brick of the baking ladle. After the nozzle is replaced, the baking ladle can be directly put on line for use without baking, and sand can be added directly, which greatly improves the overall on-line turnover efficiency of the ladle, and at the same time avoids the decline in the self-opening rate of the baking ladle caused by excessive moisture.

[0022] 2) During the heat load period of the drainage sand of the present invention, after the diatomaceous earth absorbs moisture, as the heat is transferred, the internal temperature of the drainage sand increases, the gas partial pressure of water continues to increase, and it is absorbed by CaO in the light-burned dolomite during the dispersion process and quickly hydrates, forming cracks inside the drainage sand, which can reduce the flexural and compressive strengths of the sintered layer of the drainage sand, and is conducive to the static pressure of molten steel breaking through the sintered layer to realize automatic pouring of the ladle.

[0023] 3) The diatomite used in the present invention has a refractoriness of more than 1650°C, is a powdery, porous, lightweight material, and has a thermal conductivity of 0.0219W / m·K at 800°C. An appropriate amount of diatomite can be introduced into the drainage sand and evenly mixed between the drainage sand particles. It is a good heat-resistant and heat-insulating material in the drainage sand, which can effectively reduce the internal heat flux of the drainage sand during the retention of molten steel and delay the occurrence of excessive sintering of the drainage sand. For ladles with complex processing technology and long retention time of molten steel, the self-opening rate is particularly significantly improved, reaching about 97%, and the preparation time for the ladle is shortened to about 12 minutes, with the efficiency improved by more than 1 times. DETAILED DESCRIPTION

[0024] In order to better understand the present invention, the content of the present invention is further clearly set forth in conjunction with the embodiments below, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are provided in order to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details.

[0025] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0026] Unless otherwise specified, all raw materials are from commercially available products and do not contain other unspecified components except inevitable impurities unless otherwise specified.

[0027] In the following implementation scheme, the chromium ore contains Cr2O3 in a weight percentage of ≥45%, Fe2O3 in a weight percentage of ≤28%, Al2O3 in a weight percentage of ≤16%, MgO in a weight percentage of ≤9%, and has a particle size of 0.2 mm-0.5 mm.

[0028] The weight percentage of SiO2 in quartz sand is ≥95%, and the particle size is 0.3mm-1.5mm.

[0029] The weight percentage of ZrO2 in zircon sand is ≥58%, the weight percentage of SiO2 is ≤38%, and the particle size is 0.1mm-0.5mm.

[0030] The weight percentage of MgO in fused magnesia is ≥97%, and the particle size is 0.3mm-1.5mm.

[0031] The light-burned dolomite sand contains MgO at a weight percentage of ≥55%, CaO at a weight percentage of ≥38%, and a particle size of 0.3mm-1.5mm.

[0032] Diatomite contains SiO2 weight percentage ≥ 88%, Al2O3 weight percentage ≤ 8%, bulk density ≤ 0.5g / cm 3 , particle size is 0.1mm-0.5mm.

[0033] The calcium slag contains CaO in a weight percentage of ≥55%, Al2O3 in a weight percentage of ≤38%, SiO2 in a weight percentage of ≤2%, and MgO in a weight percentage of ≤2%.

[0034] The weight percentage of SiO2 contained in the expanded perlite is ≥70%, the weight percentage of Al2O3 contained is ≤15%, the weight percentage of H2O contained is ≤0.1%, and the particle size is 0.15mm-0.5mm.

[0035] Carbonaceous materials contain C 固 The weight percentage is ≥98%.

[0036] Example 1: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 75 parts of chromium ore sand, 19 parts of lightly burned dolomite sand, 5 parts of diatomaceous earth, and 1 part of carbonaceous material. The carbonaceous material is carbon black.

[0037] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing chromium ore sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 300°C. The moisture content of the dried product is less than 0.1%. The product is naturally cooled to below 60°C to obtain a finished product, which is then measured and packaged as needed.

[0038] Example 2: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 75 parts of quartz sand, 20 parts of lightly burned dolomite sand, 3 parts of diatomaceous earth, and 2 parts of carbonaceous material. The carbonaceous material is flake graphite.

[0039] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing quartz sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 200°C. The moisture content of the dried product is less than 0.1%. The product is naturally cooled to below 60°C to obtain a finished product, which is then measured and packaged as needed.

[0040] Example 3: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 40 parts of quartz sand, 30 parts of zircon sand, 23 parts of lightly burned dolomite sand, 4 parts of diatomaceous earth, and 3 parts of carbonaceous material. The carbonaceous material is carbon black.

[0041] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing at least one of chromium ore sand, quartz sand, zircon sand and fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 450°C. The moisture content of the dried product is less than 0.1%. Cool the product naturally to below 60°C to obtain the finished product, which is then measured and packaged as needed.

[0042] Example 4: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 15 parts of chromium ore sand, 10 parts of quartz sand, 50 parts of fused magnesia sand, 17 parts of light-burned dolomite sand, 6 parts of diatomaceous earth, and 2 parts of carbonaceous material. The carbonaceous material is a mixture of carbon black and flake graphite, and the weight ratio of the two is 1:1.

[0043] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing at least one of chromium ore sand, quartz sand, zircon sand and fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 260°C. The moisture content of the dried product is less than 0.1%. Cool the product naturally to below 60°C to obtain the finished product, which is then measured and packaged as needed.

[0044] Example 5: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 50 parts of quartz sand, 30 parts of fused magnesia sand, 12 parts of lightly burned dolomite sand, 7 parts of diatomaceous earth, and 1 part of carbonaceous material. The carbonaceous material is a mixture of carbon black and flake graphite, and the weight ratio of the two is 1:3.

[0045] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing quartz sand, fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 370°C. The moisture content of the dried product is less than 0.1%. Cool the product naturally to below 60°C to obtain the finished product, which is then measured and packaged as needed.

[0046] Example 6: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 40 parts of chromium ore sand, 40 parts of fused magnesia sand, 10 parts of lightly burned dolomite sand, 7 parts of diatomaceous earth, and 3 parts of carbonaceous material. The carbonaceous material is a mixture of carbon black and flake graphite, and the weight ratio of the two is 3:1.

[0047] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing chromium ore sand, fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 400°C. The moisture content of the dried product is less than 0.1%. The product is naturally cooled to below 60°C to obtain a finished product, which is then measured and packaged as required.

[0048] Example 7: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 50 parts of zircon sand, 20 parts of fused magnesia sand, 25 parts of light-burned dolomite sand, 3 parts of diatomaceous earth, and 2 parts of carbonaceous material. The carbonaceous material is carbon black.

[0049] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing zircon sand, fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 420°C. The moisture content of the dried product is less than 0.1%. The product is naturally cooled to below 60°C to obtain a finished product, which is then measured and packaged as required.

[0050] Example 8: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 53 parts of chromium ore sand, 20 parts of quartz sand, 5 parts of zircon sand, 15 parts of lightly burned dolomite sand, 6 parts of diatomaceous earth, and 1 part of carbonaceous material. The carbonaceous material is flake graphite.

[0051] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing chromium ore sand, quartz sand, zircon sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 280°C. The moisture content of the dried product is less than 0.1%. The product is naturally cooled to below 60°C to obtain a finished product, which is then measured and packaged as required.

[0052] Example 9: A drainage sand for a baking bag is made of the following raw materials in parts by weight: 30 parts of chromium ore sand, 18 parts of quartz sand, 20 parts of zircon sand, 5 parts of fused magnesia sand, 5 parts of light-burned dolomite sand, 21 parts of diatomaceous earth, and 4 parts of carbonaceous material. The carbonaceous material is flake graphite.

[0053] The method for preparing the drainage sand for the supplementary baking bag comprises the following steps: Step S1: providing chromium ore sand, quartz sand, zircon sand, fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product at an air supply temperature of 350°C. The moisture content of the dried product is less than 0.1%. Cool the product naturally to below 60°C to obtain the finished product, which is then measured and packaged as needed.

[0054] The effective ingredients of the drainage sand prepared in the above Examples 1-9 are shown in the following table: Comparative Example 1: This comparative example is a drainage sand, which is different from Example 1 in that diatomite is omitted, lightly burned dolomite sand is 24 parts by weight, and the remaining raw materials and their weight parts are the same as those in Example 1. The preparation method thereof is referred to Example 1.

[0055] Comparative Example 2: This comparative example is a drainage sand, which is different from Example 2 in that diatomite is omitted, lightly burned dolomite sand is 23 parts by weight, and the remaining raw materials and their weight parts are the same as those in Example 2. The preparation method thereof is referenced to Example 2.

[0056] Comparative Example 3: This comparative example is a drainage sand, which is different from Example 3 in that: 10 parts by weight of light-burned dolomite sand, 17 parts by weight of diatomaceous earth, and the remaining raw materials and their weight parts are the same as those in Example 3. The preparation method thereof is referenced to Example 3.

[0057] Comparative Example 4: This comparative example is a drainage sand, which is different from Example 4 in that: 9 parts by weight of light-burned dolomite sand, 14 parts by weight of diatomaceous earth, and the remaining raw materials and their weight parts are the same as those in Example 4. The preparation method thereof is referred to Example 4.

[0058] Comparative Example 5: This comparative example is a drainage sand, which is different from Example 5 in that the lightly burned dolomite sand is omitted, the diatomaceous earth is 19 parts by weight, and the other raw materials and their weight parts are the same as those in Example 5. The preparation method thereof is referred to Example 5.

[0059] Comparative Example 6: This comparative example is a drainage sand, which is different from Example 6 in that diatomite is omitted, 17 parts by weight of lightly burned dolomite sand is used, and the remaining raw materials and their weight parts are the same as those in Example 6. The preparation method thereof is referred to Example 6.

[0060] Comparative Example 7: This comparative example is a drainage sand, which is different from Example 7 in that calcium slag is used instead of light-burned dolomite sand. The preparation method thereof is referenced to Example 7.

[0061] Comparative Example 8: This comparative example is a drainage sand, which is different from Example 8 in that expanded perlite is used instead of diatomaceous earth. The preparation method thereof is similar to that of Example 8.

[0062] Comparative Example 9: This comparative example is a drainage sand, which is different from Example 9 in that: 8 parts by weight of light-burned dolomite sand, 17 parts by weight of diatomaceous earth, and the remaining raw materials and their weight parts are the same as those in Example 9. The preparation method thereof is referenced to Example 9.

[0063] The effective ingredients of the drainage sand prepared in the above comparative examples 1-9 are shown in the following table: The drainage sand prepared in the above Examples 1-9 and Comparative Examples 1-9 was used for drainage operations of different supplementary baking bags, and the preparation time and self-opening rate of the supplementary baking bags in the drainage operations were counted.

[0064] Ladle preparation time refers to the time from the hot repair of the ladle (including the replacement of the nozzle) to the completion of the sand filling of the ladle and the preparation for the casting on the line. This time interval includes the maintenance, preparation and final sand filling of the ladle, and is an important link in the steelmaking continuous casting process. The length of the ladle preparation time will affect the production efficiency of the steel plant and the casting rhythm of the continuous casting machine. If the ladle preparation time is long, it may cause the continuous casting machine to wait, affecting the continuity of the production process. Therefore, steel mills usually try to shorten the ladle preparation time to improve production efficiency.

[0065] The test and statistical results of the present invention are as follows: The above data show that under the same number of test furnaces, the self-opening rate of the drainage sand of the present invention is significantly improved, and can reach an average of about 97%; at the same time, under a higher self-opening rate, the drainage sand of the present invention is used to prepare the seat bricks for the baking bag in a shorter time, an average of less than 12 minutes, which is at least half the time of the control example, and the operating efficiency is more than doubled, showing significant superiority.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A drainage sand for baking bag, characterized in that: The invention is made of the following raw materials in parts by weight: 0-75 parts of chromium ore, 0-75 parts of quartz sand, 0-50 parts of zircon sand, 0-50 parts of fused magnesia, 10-25 parts of light-burned dolomite sand, 3-7 parts of diatomaceous earth, 1-3 parts of carbonaceous material, and contains at least one of chromium ore, quartz sand, zircon sand and fused magnesia.

2. The drainage sand for baking bag according to claim 1, characterized in that: The chromium ore contains Cr2O3 in a weight percentage of ≥45%, Fe2O3 in a weight percentage of ≤28%, Al2O3 in a weight percentage of ≤16%, MgO in a weight percentage of ≤9%, and has a particle size of 0.2 mm-0.5 mm.

3. A drainage sand for baking bag according to claim 2, characterized in that: The weight percentage of SiO2 contained in the quartz sand is ≥95%, and the particle size is 0.3mm-1.5mm.

4. The drainage sand for baking bag according to claim 3, characterized in that: The zircon sand contains ZrO2 in a weight percentage of ≥58%, SiO2 in a weight percentage of ≤38%, and a particle size of 0.1 mm-0.5 mm.

5. The drainage sand for baking bag according to claim 4, characterized in that: The fused magnesia contains MgO at a weight percentage of ≥97% and a particle size of 0.3 mm to 1.5 mm.

6. The drainage sand for baking bag according to claim 5, characterized in that: The light-burned dolomite sand contains MgO in a weight percentage of ≥55%, CaO in a weight percentage of ≥38%, and has a particle size of 0.3 mm-1.5 mm.

7. The drainage sand for baking bag according to claim 6, characterized in that: The diatomite contains SiO2 by weight ≥ 88%, Al2O3 by weight ≤ 8%, and a bulk density ≤ 0.5 g / cm 3 , particle size is 0.1mm-0.5mm.

8. The drainage sand for baking bag according to claim 7, characterized in that: The carbonaceous material is any one of carbon black or flake graphite or a mixture of the two, containing C 固 The weight percentage is ≥98%.

9. The drainage sand for baking bag according to claim 8, characterized in that: The effective ingredients of the drainage sand for baking supplement are as follows: MgO: 6.0%-65.0%, SiO2: 3.0%-85.0%, ZrO2: 0%-30.0%, Cr2O3: 0%-34.0%, Fe2O3: 0%-21.0%, CaO: 3.5%-10.0%, Al2O3: 0.2%-12.5%, and the rest are unavoidable impurities.

10. A method for preparing drainage sand for baking bag according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1: providing at least one of chromium ore sand, quartz sand, zircon sand and fused magnesia sand, light-burned dolomite sand and diatomaceous earth, mixing them according to a proportion, and stirring to obtain a mixture; Step S2: adding carbonaceous material to the mixture, stirring and mixing again to obtain a semi-finished product; Step S3: Dry the semi-finished product to a moisture content of less than 0.1% after drying, and cool it naturally to below 60°C to obtain the finished product, which is then measured and packaged as required.

Citation Information

Patent Citations

  • Manufacturing method for ladle filler sand and filling method for filling land filler sand into steel ladle

    CN106513655A

  • Operation method for improving self-opening rate of ladle filler sand

    CN118699354A

  • Casting mold material composition

    JP2016215221A

  • Molten metal-feeding space-forming member

    JP2024106916A